Determinan Keputusan Menikah Dini Remaja Perempuan di Kota Malang - Ratih Agustin Rachmaningrum; Ritna Sandri; Nurjin Lanang Wibawa (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Early-age marriage has serious implications for public health. Marriage requires thorough preparation from the couple so that the family built is of high quality and lasting. The purpose of this research is to identify and analyze the influence of fatherlessness, emotional regulation, and self-control on early-age marriage decisions. This study uses quantitative method with regression analysis. The sampling technique used purposive sampling, and sample size of 102 respondents was obtained through the distribution of questionnaires to young woman’s in the Malang city, East Java Province. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of this research show that fatherlessness, emotional regulation, and self-control significantly effects to early-age marriage. The results of this research can be used as evaluation material for the government and parents to enhancing adolescent participation in PIKRs, promoting healthy marriage, and also sexuality education through social media. Furthermore, the results of this research can serve as a source of knowledge for adolescents to obtain information and understand the importance of emotional education programs for individuals who married at a young age, focus on enhancing emotional management skills, and understanding the dynamics of marital relations.